RIGHT DISPLACEMENT OF ABOMASUM IN A HOLSTEIN FRIESIAN CROSS BRED CATTLE: CLINICOPATHOLOGICAL, ULTRASONOGRAPHIC AND POST MORTEM FINDINGS - Jitendra Kumar Bairwa; D. Sumathi; G. Senthil Kumar; R. Ravi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Displacement of the abomasum is one of the important incidence recorded in dairy cattle especially after calving that lead to huge economic loss. A six year old Holstein Friesian female cow calved fifteen days back was presented to the Large Animal Outpatient Unit, Teaching Veterinary Clinical Complex, Veterinary College and Research Institute, Namakkal with the history of not voiding dung and anorexia for past three days. The animal was fed with corn and ragi feed. Clinical examination revealed pale pink mucous membranes, right side distension of abdomen, ping sound on right paralumbar fossa to 11th intercostal space on simultaneous auscultation and percussion. On rectal examination balloon like structure was noticed and the liptak test revealed pH of 2. Ultrasonographic examination of abomasal contents and post mortem examination confirmed RDA.